Selecting Optimal Modular Structures using Particle Swarm Optimization - Durán, Orlando (2010)
This paper proposes a method which helps users to change their dedicated systems gradually into modular ones. The optimization is achieved through appropriately selecting the subsets of module instances from given sets. The proposed formulation is general in the sense that products can have any number of modules. Particle swarm optimization is used to solve the optimization model. Comparative results are presented using information from exhaustive enumeration.